PENGARUH KEJELASAN SASARAN ANGGARAN DAN PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAHAN KABUPATEN BIREUEN - Saifrizal, Muhammad (JURNAL KEBANGSAAN, 2019)
ABSTRACT This study aims to determine the effect of Target Clarity Budget and Accounting System Implementation of the Regional Financial Institution Performance Accountability Bireuen District Government. Data obtained by questionnaires distributed in 15 offices SKPD Bireuen district with a total sample of 45 samples. The analysis technique used is linear regression, hypothesis testing using t-statistic, test F and test the coefficient of determination as well as the f-statistic to test the effect partially to the level of significance of 5%. The result showed that the Target Budget Clarity has a significant positive effect on Accountability is equal to 0.534. Application of Regional Financial Accounting System positive and significant impact on Accountability, with a regression coefficient of 0.737. Concurrent test results showed that the Clarity Budget Goals and Implementation Regional Financial Accounting System influence on employee performance, with a coefficient of determination of 83.7%%. Keywords: Budget Targets Clarity, SIKD Implementation, Accountability